Household food insecurity and its association with diet quality and weight status among Orang Asli (Mah Meri) women in Kuala Langat, Selangor, Malaysia - Chong, Su Pei (2018)
Socio-economic status was the main contributor of food insecurity, which was shown to be associated with poor nutritional outcomes among women. This cross-sectional study was designed to determine characteristics of houdsehold food insecurity and its association with diet quality and weight status among 222 Mah Meri women in Kuala Langat, Selangor. Respondents in this study were selected using cluster sampling method. Household food insecurity was assessed using Radimer/Cornell Hunger and Food Insecurity Instrument. Malaysian Healthy Eating Index (HEI) was used to measure the overall diet quality of the population. Data on socio-demographic, environmental sanitation and personal hygiene practices, nutrition knowledge, food security status and 24-hour dietary recalls were obtained through face-to-face interview with the respondents. Anthropometric measurements including weight, height, Body Mass Index (BMI), waist circumference and body fat percentage were conducted. In this study, majority of the Orang Asli households experienced some form of food insecurity, which were household food insecurity (29.3%), individual food insecurity (23.4%), and child hunger (30.2%). The overall diet quality of the respondents was poor, with a mean Malaysian HEI score of 45.3%. While 57.2% of the respondents were found to be overweight and obese, 53.6% were abdominally obese and 54.1% posses an overfat and obese level of body fat percentage. Child-hunger group had significantly more children (p<0.05) and larger household size (p<0.05) compared to food-secure group. There was a significant decrease in the mean household income, income per capita, total expenditure and food expenditure as food insecurity worsened (p<0.001). In addition, the child-hunger group had significantly lower mean environmental sanitation score compared to food-secure and household food-insecure groups respectively (p<0.001). The mean score of nutrition knowledge of child-hunger group was significantly lower than household food-insecure group (p<0.05). In terms of Malaysian HEI, individual food-insecure group and child-hunger group had significantly lower mean scores for components grains and cereals (p<0.01) and meat, poultry and eggs (p<0.001) as compared to food-secure and individual food-insecure groups. On the contrary, child hunger group had significantly higher mean scores of total fat (p<0.05) and sodium (p<0.001) than food-secure group. Compared to the individual food-insecure and child-hunger groups, MANCOVA showed that the food-secure group was significantly associated with a higher Malaysian HEI score while the household food-insecure group was significantly associated with a higher BMI after controlling for age and marital status (p<0.025). In conclusion, this study indicated that the majority of Mah Meri households were food insecure. The overall diet quality of the respondents was poor and more than half of them were either overweight or obese. Respondents from individual insecure and child hunger groups were associated with lower diet quality. While respondents from household insecure group were associated with higher body weight. These findings suggest a pressing need for nutrition interventions to enhance dietary intake among the low income households in the Mah Meri community in the district of Kuala Langat, Selangor.